An Evaluation Tool for Agricultural Health and Safety Mobile Applications. Issue 4 (1st October 2016) - Reyes, Iris; Ellis, Tammy; Yoder, Aaron; Keifer, Matthew C.
ABSTRACT: As the use of mobile devices and their software applications, or apps, becomes ubiquitous, use amongst agricultural working populations is expanding as well. The smart device paired with a well-designed app has potential for improving workplace health and safety in the hands of those who can act upon the information provided. Many apps designed to assess workplace hazards and implementation of worker protections already exist. However, the abundance and diversity of such applications also presents challenges regarding evaluation practices and assignation of value. This is particularly true in the agricultural workspace, as there is currently little information on the value of these apps for agricultural safety and health. This project proposes a framework for developing and evaluating apps that have potential usefulness in agricultural health and safety. The evaluation framework is easily transferable, with little modification for evaluation of apps in several agriculture-specific areas.